El control interno contable y su aporte a la razonabilidad de la cuenta clientes en el sector comercial - Barrezueta Andrade, Anibal Manuel (2015)
The present study was conducted to analyze the internal controls in the company Hotel Veuxor city of Machala , which was developed through several concepts referenced scientific reports prepared by professional writers on the subject, the methodology used was exploratory - descriptive . Its observations within the premises of the company interviewing staff of the company was conducted , as well. The results showed that the company does not have an integrated internal control system, that permits daily activities effectively in the department of Credit and Collections, so a design of a control system in the Accounts Receivable recommended enabling its specific assessment .